High manifestations of food insecurity and hunger among pregnant and lactating women during post-conflict in Tigray, Ethiopia: a community-based study - Ataklti Gebretsadik Woldegebriel; Gebremedhin Gebreegziabiher Gebrehiwot; Ataklti Gessesse Teka; Hagos Amare Gebreyesus; Tesfay Teklemariam Weldeslassie; Abraham Aregay Desta; Haftamu Kebede Yigzaw; Nega Mamo Bezabih; Haylom Kahsay Baryau; Mekonnen Haileselassie; Mengish Bahresilase Gebregziabiher (BMC, 2024)
Abstract Background Food insecurity is a state or condition in which people have limited or uncertain physical, social, and economic access to safe, sufficient, and nutritious food to meet their dietary needs. Since no thorough evaluation was carried out to determine the degree of household food insecurity in Tigrayan communities in the aftermath of the conflict. This study aims to describe household-level food insecurity status among pregnant and lactating women during the post-armed conflict in Tigray, Ethiopia. Method Descriptive research was designed to assess household food insecurity. A multi-stage sampling technique was used for this study. One thousand two hundred forty-nine households were selected systematically following a list of food insecure households. Descriptive statistical values, including frequency counts, percentages, minimum values, maximum values, and averages, were calculated to quantify the indicators under study. Household food insecurity and hunger Scale measurement using the standardized Food and Agriculture Organization standard. Results The mean age (± SD) of the mothers was 28.35 ± 5.91 years. More than three fourth of the participants 1010(80.93%) were rural residents. The survey result showed that 88.8% of the pregnant and lactating were food insecure. Half (50.1%) of the households were hungry,one month before the study, 78.5% of the families expressed concern about running out of food and 6.4% had severe hunger. Conclusions The food insecurity levels and hunger prestige of the study communities were excessively high. This is in the context of a region affected by intense armed conflict. It is commended that the study communities need to be safeguarded from the direct and long-term consequences of armed conflict-caused household food insecurity.